Use of simulation for antimicrobial stewardship Infectious Disease fellowship curriculum. (4th October 2017) - Barsoumian, Alice; White, Brian; Yun, Heather
Abstract: Background: Effective antimicrobial stewardship (AS) requires interdisciplinary teamwork, quality improvement (QI), and knowledge of systems. Simulation (sim) is used to train and evaluate learners on processes. We developed a series of simulated AS committee meetings to train infectious disease (ID) fellows in synthesis of AS interventions. Sim debriefs and fellow/faculty surveys assessed the learners and the format. Methods: 3 simulated AS committee meetings and pre-lectures were developed. Inauthentic roles were assigned with instructions to review AS literature pertinent to that role. Sims were conducted over 1.5 hours. Notional results of proposals were given, prompting new QI cycles. Sims concluded with debriefs. Individual and team performance were evaluated using a common tool. Pre and post surveys were collected from fellows and faculty members to assess the format. Results: 6 fellows participated in the series. The 3 scenario tasks were as follows: decrease Clostridium difficile rates in a hospital, decrease outpatient antibiotic prescriptions for viral infections, and improve perioperative antibiotic use via telehealth. 83.3% of fellows pre and 100% post sim series reported educating others on AS principles in the previous 1 month. Fellows commented "I enjoy the format", "the sims were very engaging", and suggested more scenarios be added into the curriculum. 8 faculty members completed pre/post surveys. 25% of faculty pre and 0% post reported that fellow attitude on the existing preauthorization process was useless/unnecessary and 37.5% of faculty pre and 62.5% post reported it was useful/necessary. No changes were seen in other areas of AS performance queried. Comments included that the approach was "fantastic, " "great, " and the fellows "take [the sim] seriously." Faculty noted that the discussion reflected actual AS committee discussion and was useful in evaluation of learners. Conclusion: Sim based training is an effective and enjoyable way to train ID fellows in AS. Fellows improved in knowledge, skills, and attitudes. Plans exist to use the series in the next academic year with senior fellows acting as moderators, and to evaluate the involvement of graduates in AS. Disclosures: All authors: No reported disclosures.